2015
DOI: 10.1186/s13104-015-1451-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the isoniazid preventive therapy (IPT) program in Shurugwi District, Midlands Province, Zimbabwe, January 2013 to August 2014

Abstract: BackgroundMidlands Province started implementing the Isoniazid (INH) preventive therapy (IPT) program in January 2013. Shurugwi and Gokwe North were the piloting district hospitals. In May 2014, four more districts hospitals (Gokwe South, Gweru, Kwekwe and Zvishavane) started implementing IPT. Shurugwi District decentralized the program to its rural health facilities in January 2014. A review of the Shurugwi IPT program, 2013 data, indicated that the majority of eligible clients were not started on IPT. None o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 6 publications
6
19
0
Order By: Relevance
“…Second, only about half of the IPT eligible PLHIV were initiated on IPT. This is within the range that has been found in other studies in Africa from 2014–2017 [15,24,25]. Our study results also showed that PLHIV who were separated or divorced were more likely to be initiated on IPT.…”
Section: Discussionsupporting
confidence: 90%
“…Second, only about half of the IPT eligible PLHIV were initiated on IPT. This is within the range that has been found in other studies in Africa from 2014–2017 [15,24,25]. Our study results also showed that PLHIV who were separated or divorced were more likely to be initiated on IPT.…”
Section: Discussionsupporting
confidence: 90%
“…IPT completion rate appears to vary across settings, subpopulations, country policy guidelines on duration of treatment, availability of incentives, and whether IPT is provided alone or prepackaged with ART. For instance, studies from Zambia, Kenya, and Ethiopia concluded that under programmatic implementation, combination of IPT with additional package of interventions such as incentives for patient travel reimbursement, training of health-care workers, provision of Information, Education and Communication (IEC) materials and Standard Operating Procedure (SOPs), quality adherence counseling by physicians, patient follow-up, and continuous quality improvement have higher completion rate,[ 3 10 11 12 13 ] compared with implementation not combined with the above package of interventions. [ 14 ]…”
Section: B Ackground /R Ationalementioning
confidence: 99%
“…In order for South Africa to reduce the incidence of TB from 9800 per million in 2010 to 1500 per million in 2050 and TB-associated mortality from 2180 per million in 2010 to 200 per million in 2050, IPT must be scaled up to 75% by 2035 [32]. Many other studies across Africa reported rates ranging from 54% in a health district of Zimbabwe [33] to 77% in an urban health centres of Kenya [34]. The recorded low uptakes, irrespective of the geographical settings, have been linked to patients’ related factors such as non-adherence, non-disclosure of HIV serostatus and lack of social support [35, 36] and health care related factors such as the levels of knowledge of the health care providers, and facilities being out of stock, amongst others [33, 37].…”
Section: Introductionmentioning
confidence: 99%